RETRACTED: Effects of “Mindfulness Acceptance Insight Commitment” Training on Flow State and Mental Health of College Swimmers: A Randomized Controlled Experimental Study - Ning, Jun-hui; Hao, Qing-wei; Huang, Da-cai (Frontiers in Psychology, 2022)
This research explores the intervention effect of the mindfulness acceptance insight commitment (MAIC) training program on mindfulness level, flow state, and mental health of college swimmers. A sample of 47 college swimmers from a regular university was recruited and randomly divided into two groups before the intervention. Independent variables between groups are psychological training mode (MAIC training / no training) and within the groups are time-related: Pre-test (T1), Post-test (T2), Continuity test (T3), that is, ten weeks after the intervention. Dependent variables are mindfulness level, flow state, and mental health (anxiety, depression, training and competition satisfaction). Results show that after the intervention of MAIC training, the mindfulness level of athletes’ flow state has been significantly improved, whereas anxiety and depression significantly decreased. In addition, the satisfaction with training and competition significantly improved . In the continuous stage after the intervention, the mindfulness level, flow state, and mental health of athletes are still significantly higher than those in the Pre-test. Comparison of Post-test and Continuity test show no significant differences in mindfulness level, flow state, depression, training and competition satisfaction of athletes. Still, the anxiety level shows an upward trend with a significant difference. This study demonstrates that MAIC mindfulness training program can significantly improve the mindfulness level, flow state, anxiety, depression, and training and competition satisfaction of college swimmers with a good continuity effect. Thus, the athletes’ sports experience can be improved, and good psychological benefits can be attained.